The Effect of Product Quality, Price, And Promotion on Purchase Decision at Ud Swasta Nulus Printing - I Gusti Ketut Agung Pramesta Abhirama; I Gst. Ngurah Jaya Agung Widagda K (International Forum of Researchers and Lecturers, 2025)
The decline in sales of UD Swasta Nulus in the 2022–2024 period and the increasing competition in the printing business in Denpasar City are phenomena related to consumer purchasing decisions. This study aims to analyze the influence of product quality, price, and promotion on consumer purchasing decisions of UD Swasta Nulus in Denpasar. This study is associative-causal with a quantitative approach. The study population consisted of 385 active consumers, with a sample of 80 respondents determined using the Slovin formula. Primary data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression. The results showed that product quality had a positive and significant effect on purchasing decisions. The price variable also had a positive and significant effect on purchasing decisions. In addition, promotion had the most dominant influence on purchasing decisions, with the highest beta value and coefficient compared to other variables. Simultaneously, the three independent variables had a positive and significant effect on consumer purchasing decisions of UD Swasta Nulus. This study enriches the empirical discourse in service marketing management, particularly in the printing sector, by emphasizing the importance of the marketing mix consisting of product quality, price, and promotion in shaping consumer purchasing decisions. Practically, these findings are expected to provide insights for UD Swasta Nulus in formulating more effective marketing strategies, especially through improving print quality, setting competitive prices, and strengthening digital-based promotional strategies to reach wider consumer segments.